2017
DOI: 10.1186/s12891-017-1488-2
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term outcome following revision surgery of clavicular non- and malunion using anatomic locking compression plate and iliac crest bone graft

Abstract: Background: Treatment of clavicular non-and malunion is still challenging. Current surgical procedures often result in frustrating functional outcome along with high-grade subjective impairment and increased rates of revision surgery. However, the combination of biological augmentation with vital bone graft and a biomechanically sufficient fixation system seems to be a promising concept of treatment. Methods: In this retrospective study, 14 patients with a mean age of 44 years (26-67 years) suffering from non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…However, the majority of clavicle Fx can still be treated conservatively, although there has been a clear trend towards operative treatment in the last years [ 1 ]. One major complication of conservative treatment in clavicle Fx still is a high rate of non-union (15.1%), which is significantly higher as compared to operative treatment (2.2%) [ 6 , 7 ]. Furthermore, 15.3% of 122 conservatively treated patients with clavicle fractures were reported with a poor functional outcome after a mean follow-up of 2.7 years [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of clavicle Fx can still be treated conservatively, although there has been a clear trend towards operative treatment in the last years [ 1 ]. One major complication of conservative treatment in clavicle Fx still is a high rate of non-union (15.1%), which is significantly higher as compared to operative treatment (2.2%) [ 6 , 7 ]. Furthermore, 15.3% of 122 conservatively treated patients with clavicle fractures were reported with a poor functional outcome after a mean follow-up of 2.7 years [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Particularly when nonunion resection creates a bony defect, bone graft addition is required. It has been reported that a clavicular defect of over 1.5 cm benefits from bony bridging [ 3 , 4 ]. According to Wei and Mardini, bone defects up to 5 cm can be bridged by non-vascularized bone grafts [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, symptomatic pseudarthrosis is primarily surgically treated. Convincing healing results can be achieved by applying different plate configurations and plate localizations, usually combined with bone grafts [ 31 , 32 , 33 , 34 ]. However, a decisive disadvantage is the invasive nature of the intervention in clavicle non-union revision surgery, which is associated with all common complications of surgery.…”
Section: Introductionmentioning
confidence: 99%
“…However, a decisive disadvantage is the invasive nature of the intervention in clavicle non-union revision surgery, which is associated with all common complications of surgery. These may include, but are not limited to, plate loosening or implant failure, infection, sensory disturbance, shoulder stiffness, the need for removal if the osteosynthesis material is symptomatic, and the risk of refracture after removal [ 31 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%